2022
DOI: 10.1093/stmcls/sxac033
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like Factor 4 Supports the Expansion of Leukemia Stem Cells in MLL-AF9-driven Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) is an aggressive malignancy of the bone marrow with five-year overall survival of less than 10% in patients over the age of 65. Limited progress has been made in the patient outcome because of the inability to selectively eradicate the leukemic stem cells (LSC) driving the refractory and relapsed disease. Herein, we investigated the role of the reprogramming factor KLF4 in AML because of its critical role in the self-renewal and stemness of embryonic and cancer stem cells. Using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…In line with our earlier observations, we found that the expression levels of numerous mRNAs associated with the development of leukemia, including Dusp6 , 27 Klf4 , 28 and Plxnb2 , 29 were significantly elevated in ECs and resting leukemia cells after chemotherapy (Fig. 4D).…”
Section: Resultssupporting
confidence: 92%
“…In line with our earlier observations, we found that the expression levels of numerous mRNAs associated with the development of leukemia, including Dusp6 , 27 Klf4 , 28 and Plxnb2 , 29 were significantly elevated in ECs and resting leukemia cells after chemotherapy (Fig. 4D).…”
Section: Resultssupporting
confidence: 92%
“…These experiments were, however, performed in immunodeficient mouse models, and a putative innate immune response to NKG2D-L positive AML was not addressed. KLF4 is one of the Yamanaka factors able to induce pluripotent stem cells and was recently shown to promote leukemia stem cell division and stemness [ 35 ]. This finding may seem paradoxical but makes sense considering that the NKG2D-L expression is an early cellular response to malignant transformation in order to alert the innate immune system to dangerous cells – which is characterized by high KLF4 expression.…”
Section: Discussionmentioning
confidence: 99%